\(G=\left(x+y+z\right)^3-\left(x+y-z\right)^3-\left(-x+y+z\right)^3-\left(x-y+...">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

26 tháng 2 2017

Dat  (x-y)2+(y-z)2+(x-z)2=A

=(x+y)3+z3-3x2y-3xy2-3xyz / A

=(x+y+z).(x2+2xy+y2-xy-yz+z2)-3xy(x+y+z) / A

=(x+y+z).(x2+y2+z2-xy-yz-xz) /A

=2(x+y+z).(x2+y2+z2-xy-yz-xz) /2A 

=(x+y+z)[ (x2-2xy+y2)+(y2-2yz+z2)+(x2-2xz+z2) / 2A

=(x+y+z).[ (x-y}2+(y-z)2+(x-z)] /2A

=(x+y+z). A /2A

=x+y+z /2

26 tháng 2 2017

kimh thế

12 tháng 8 2020

quy đồng mẫu thức ta được

\(\frac{yz\left(z-y\right)+xz\left(x-z\right)+xy\left(y-x\right)}{xyz\left(x-y\right)\left(y-z\right)\left(z-x\right)}\)\(=\frac{yz\left(z-y\right)+xz\left(x-z\right)-xy\left[\left(z-y\right)+\left(x-z\right)\right]}{xyz\left(x-y\right)\left(y-z\right)\left(z-x\right)}\)

\(=\frac{y\left(z-y\right)\left(z-x\right)+x\left(x-z\right)\left(z-y\right)}{xyz\left(x-y\right)\left(y-z\right)\left(z-x\right)}=\frac{\left(z-y\right)\left(z-x\right)\left(y-x\right)}{xyz\left(z-y\right)\left(z-x\right)\left(y-x\right)}=\frac{1}{xyz}\)